SOSIALISASI PENYIMPANAN DAN KEAMANAN DOKUMEN REKAM MEDIS PADA RUANG FILLING DI KLINIK PANACEA BATAM - Situmorang, Masriani; Mulyana (Transpublika Publisher, 2022)
The Panacea Clinic is a level I health facility for referral patients, the Panacea clinic has a place to store medical records. However, the storage area does not yet have security in accordance with existing regulations. This community service activity aims to socialize concepts and regulations related to storing, filing and securing medical record documents (DRM). This activity is carried out exclusively with socialization-based methods. Fifteen people participated in this activity, including employees from related departments at Panacea Clinic and students of Awal Bros University. As a result, the program becomes more interactive, as participants can ask questions and engage in discussions regarding DRM storage and security systems. In accordance with what was outlined in the PPT format for the dissemination and delivery of information regarding DRM storage, filing, and security systems, the achievement of the objective material discussed by the speakers indicated that all information had been submitted. This can be seen from the participants' understanding of the topic as indicated by the results of the pre-test and post-tests. The conclusion of this program is that the participants' understanding of the material provided has been achieved, as evidenced by the average posttest result score which increased from 80 to 99. In the future mentoring activities will be carried out related to the implementation of DRM storage, alignment, and security activities so that this community service activity will continue.